Facile fabrication of polysiloxane micro/nanostructure with controllable morphology and super-hydrophobicity. (20th January 2021) - Xi, Yanni; Sun, Yi; Li, Wulong; Li, Zhanxiong
Abstract: In this study, hydrophobic fabrics with controllable rough surfaces were prepared by treating a polyester (PET) fabric with methyltrichlorosilane (MTS), phenyltrichlorosilane (PTS), vinyltrichlorosilane (VTS), and tridecylfluorooctyltrichlorosilane (PFOTS) using a liquid phase method. The formation mechanism of the fabrics was investigated using X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Although the WCA of the fabrics decreased after mechanical abrasion, their hydrophobic surfaces exhibited good durability. Four controllable rough structures were observed and show its unique properties. MTS@PET showed a hollow spherical structure, and hence was found to have potential to encapsulate medicines for health care. On the other hand, PTS@PET showed a hollow bowl-like structure and strong absorbance to water. The TCS/PFOTS@PET with spherical microstructure was amphiphobic, according to that the contact angles of it to water and n -tetradecane were 153.3 ± 3.0° and 133.4 ± 4.5°, respectively. The WCA and sliding angle (SA) of VTS@PET, which showed a nanofilament structure, were 156.4 ± 3.0° and 3.0 ± 2.0°, respectively, indicating that its surface was superhydrophobic. Graphical abstract: Image 1 Highlights: Four kinds of trichlorosilanes were used to finish PET fabrics via simple liquid phase method. Rough structure was constructed on the fiber surface and the formation mechanism was proposed. The surface morphology of treated fibers was diverse and controllable. Super-hydrophobic and/or oleophobic fabrics were produced using different silane monomers as finishing agent.